A genetic off‐target event in a site‐specific integration cell line expressing monoclonal antibody has no impact on commercial suitability. (19th January 2023) - Tevelev, Barbara; Chambers, Andre; Ghosh, Swap; Zhang, Ying; Marzili, Lisa; Rouse, Jason C.; Han, Shu; Moffat, Mark; Scarcelli, John J.
Abstract: Site‐specific integration (SSI) cell line systems are gaining popularity for biotherapeutic development and production. Despite the proven advantages for these expression hosts, the SSI system is still susceptible to rare off‐target events and potential vector rearrangements. Here we describe the development process of an SSI cell line for production of an IgG1 monoclonal antibody (mAb‐086). During cell line generational studies to assess suitability of clone C10 for commercial purposes, restriction fragment lengths of genomic DNA harboring the light chain (LC) were not in agreement with the predicted size. We first confirmed that the SSI landing‐pad achieved occupancy of the desired expression plasmid. Additional investigation revealed that random integration had occurred, resulting in the acquisition of a partial copy of the LC and a full‐length copy of the heavy chain (HC) at a different locus in the host genome. This off‐target event had no impact on the genotypic consistency and phenotypic stability of the cell line, the production process, or the drug substance product quality. Given the genetic, phenotypic, and process consistency of the cell line, clone C10 was deemed suitable as a manufacturing cell line.